Enhanced piezoelectric energy harvesting system model leveraging phase shifting effects for optimization - Thong, Li Wah; Kok, Swee Leong; Ramlan, Roszaidi (International Information and Engineering Technology Association, 2023)
Conventional piezoelectric cantilever beams experience limited operating bandwidth and reduced output power due to phase angle changes post-resonance. The phase shifting phenomenon between excitation and responses in piezoelectric cantilever beams is a critical factor in energy conversion efficiency. In this study, an equivalent circuit model for a multi-mode vibration energy harvesting system is presented, incorporating various electrical configurations to improve performance in terms of power output and bandwidth through phase shifting effects. The analytical modeling and experimental results of the proposed configurations demonstrate a significant increase in output power, particularly between intersections of successive peaks when the reverse polarity series connection is incorporated into the system. The phase difference between two cantilever beams is significantly reduced due to polarity changes, thereby boosting output voltage in the suggested configurations. The obtained frequency response output indicates that by alternating the polarities of the series connections in the vibration energy harvester, the output power between the valley of two successive frequencies at resonance for the energy harvesting system can be increased by up to 76 percent. This paper highlights the potential of leveraging phase shifting effects to optimize piezoelectric energy harvesting systems.